Gender and Self Regulated Learning During COVID-19 Pandemic in Indonesia - Tommy Tanu Wijaya; Zhou Ying; Lin Suan (Universitas Pahlawan Tuanku Tambusai, 2020)
A new coronavirus has been found to cause the outbreak of the COVID-19 pandemic. COVID-19 is an infectious disease caused by a newly discovered coronavirus. This is a new virus and a disease. It has not been discovered before the outbreak in Wuhan, China, in December 2019. The COVID-19 pandemic stopped teaching activities for a while. Students conduct learning activities independently in their homes. The purpose of this study was to compare the self-regulated learning of male and female students in the 19 Indonesian epidemic. This research uses quantitative and survey methods, and the research object is primary school students in Indonesia. The self-regulated learning questionnaire has been shared online. The results of this study show that powerful dynamic mathematics software has an impact on the learning autonomy of the covid-19 pandemic. In the co-population 19 pandemic, self-regulating female students are better than male students in learning.